Post-vaccination Streptococcus pneumoniae colonization and respiratory manifestations in children: A prospective cohort study - Jaqueline Elisa Verardo Benedetti; Kauana Pizzutti; Mariana Preussler Mott; Pedro Uriel Pedrotti Vieira; Neide Maria Bruscato; Emilio Hideyuki Moriguchi; Roberta Rigo Dalla Corte; João Carlos Batista Santana; Cícero Dias (PLoS ONE, 2025)
Background Streptococcus pneumoniae is considered one of the main agents for pneumonia, meningitis, bacteremia, sinusitis, and acute otitis media (AOM)especially in children under 5 years, and a cause for morbidity and mortality due to respiratory infections worldwide. Our aim was to investigate the influence of Streptococcus pneumoniae colonization in vaccinated children regarding infections in a one-year follow-up. Methods A double-blind, observational, prospective cohort study was conducted on children aged 18–59 months, vaccinated with pneumococcal conjugate vaccine 10 (PCV10) or pneumococcal conjugate vaccine 13 (PCV13). A total of 225 children were monitored, with different dates of entry into the study, which occurred between March 2018 and October 2019 (zero time). At the end of one year, counting from the date of entry, interviews and data collection took place in medical records (end of follow-up). The Poisson regression with robust variance and Chi-squared or Fisher’s exact tests were used for qualitative analyses; Mann-Whitney or Friedman tests for quantitative analyses. Results A high colonization rate (64.4%) was observed, with only 2.8% of carriers having a PCV10 vaccine serotype, specifically 6B, as expected. Being male showed association to colonization (p = 0.05). We found that children colonized by pneumococcus do not have an increased risk for respiratory diseases or antimicrobial use. Exception was only observed in cases of serotype 6B colonization, showing association with pneumonia in children under 2 years (p = 0.016). Conclusion Our study reveals that the carriage of Streptococcus pneumoniae does not appear to significantly impact the incidence of respiratory diseases in a fully-vaccinated children population. However, it is noteworthy that a correlation was observed in the occurrence of pneumonia in children under the age of 2 when colonized by serotype 6B.